Palatine Tonsilloliths and Actinomyces: A Multi‐institutional Study of Adult Patients Undergoing Tonsillectomy. (5th May 2020) - Arvisais‐Anhalt, Simone; Quinn, Andrew; Bishop, Justin A.; Wang, Cynthia S.; Mitchell, Ron B.; Johnson, Romaine F.; Schultz, Barbara; Day, Andrew T.
Abstract : Objective: To better characterize associations between Actinomyces and tonsillolith versus nontonsillolith tonsillectomy specimens. Study Design: Bi‐institutional retrospective case‐case study. Setting: University and county hospital. Subjects and Methods: Adult patients with a clinical history of tonsilloliths who underwent tonsillectomy from January 2006 to December 2018 were included. Patients undergoing tonsillectomy for tonsillar hypertrophy and chronic tonsillitis were identified as comparative cases. Similarly, patients with ipsilateral oropharyngeal cancer (OPC) who underwent contralateral tonsillectomy of a normal‐appearing tonsil for prophylaxis against a second primary cancer were also included as comparative cases. Results: The study population comprised 134 patients who underwent tonsillectomy: 62 tonsillolith and 72 nontonsillolith (tonsillar hypertrophy, n = 30; chronic tonsillitis, n = 30; normal‐appearing contralateral tonsil in patients with ipsilateral OPC, n = 12). Actinomyces was reported in 11% of the patients with tonsilloliths on initial pathology reports but in 95% after re‐evaluation (n = 54 of 57). Actinomyces prevalence was significantly higher in patients with tonsilloliths as compared with patients with recurrent tonsillitis (73%, n = 22 of 30, P <. 001) and normal‐appearing contralateral tonsils in patients with ipsilateral OPC (58%, n = 7 of 12, P <. 001). Actinomyces prevalence was not significantly different between patients with tonsilloliths and tonsillar hypertrophy (83%, n = 25 of 30, P =. 11). Conclusion: The prevalence of Actinomyces in tonsillolith tonsil specimens is high; however, Actinomyces routinely colonizes nontonsillolith tonsil specimens. Therefore, Actinomyces is unlikely to be the primary driver of tonsillolith pathogenesis, and Actinomyces‐ targeted treatment of tonsilloliths may not be effective. Treatment strategies addressing tonsilloliths should be further investigated.